Totally ultrasound-guided minimally invasive percutaneous nephrolithotomy in children: Is it safe? - Ali Eslahi; Mohammad Mehdi Hosseini; Faisal Ahmed; Delara Tanaomi; Seyyed Hossein Hosseini; Mohammad Reza Askarpour; Hossein-Ali Nikbakht; Khalil Al-Naggar (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of the study was to assess the outcome and feasibility of ultrasonography (US)-guided minimally invasive percutaneous nephrolithotomy (mini-PCNL) in children. Materials and Methods: Twenty-five children with upper urinary tract stones who had undergone US-guided mini-PCNL from June 2017 to June 2020 were enrolled in this study. Patients' demographic information and post-treatment results were retrospectively gathered and analysed. Pyelocaliceal system was punctured in prone position using US guidance, and the tract was dilated using single-shot dilation technique. All steps of renal access were done using only US. Mini-PCNL in all cases was done by using 15 Fr rigid nephroscope. Stones were fragmented with a pneumatic lithotripter and evacuated. Results: The patients' mean age was 6.30 ± 3.25 years (range: 1.5-15). The mean stone size was 16.04 ± 3.93 mm (range: 10-30). The mean access time to the stone was 1.50 ± 0.62 min (range: 1-4). The mean operation time was 94.66 ± 3.05 min (range: 90-100 min). The final stone-free rate was 96%. Post-operation fever occurred in 4 (16%) patients who were treated successfully with an antibiotic. No major complications occurred. Conclusions: We recommend US-guided mini-PCNL as a harmless alternative treatment option, in children with renal calculi due to its excellent outcomes and little complications.